(untitled) (SciELO Preprints, 2020)
Intensive care units (ICUs) have adopted flexible visitation models as a way to favor care focused on the needs of patients and their families. AIM: To evaluate an extended visitation model in an adult ICU from the perspective of family members and the care staff. METHODS: Cross-sectional study. This study was carried out with family members of patients and care staff in a general ICU with an extended visitation model in a hospital in the south of Brazil. The evaluation of the extended visitation policy was performed through a 22-question survey. RESULTS: The answers of 95 accompanying family members and 95 members of the ICU care team were analyzed. Members of the nursing staff evaluated as negative the changes in attitudes at work (77.9%), believe that work is interrupted (46.3%); and consider that it contributes little to decreasing anxiety and stress in the family. The accompanying family members evaluated the following issues more positively: decreased anxiety and stress in the family (91.6% versus 58.9%;p <0.01); family members get more information (86.3% versus 64.2%; p <0.01). CONCLUSION: Both groups evaluated as positive the majority of the aspects of the extended visitation model. However, the aspects that presented the greatest divergence in the evaluations, with a more negative perception from the perspective of the team members, were the interference in the work of the team, changes in attitudes at work, a lower perception of the reduction in anxiety and stress in the family and patients, and discomfort caused by the presence of a relative.